PERTUMBUHAN DAN HASIL TANAMAN WIJEN DENGAN PEMBERIAN FUNGI MIKORIZA ARBUSKULA (FMA) DAN BOKASHI TITHONIA PADA TANAH ULTISOL - Ediwirman Zaharnis .; Zaharnis . (Jurnal Agroekoteknologi, 2010)
ABSTRACTThis research aims to obtain dose combination bokashi Tithonia and more precise AMF on growth and yield of sesame in the Ultisol. This research used Completely Randomized Design with 3 replications. The treatment is given, the first factor (A) is a measure bokashi Tithonia 4 levels namely, 0, 1, 2, and 3 t ha-1. The second factor (B) is 3 levels of arbuscular mycorrhizal fungus (AMF), namely: 25, 50 and 75 g plant-1. Investigated range of advanced real test, if the F count > F Table 5% with advanced test LSD 5% level. The results showed that bokashi tithonia and mycorrhizal provides no real interaction, but a single real influence. Giving bokashi Tithonia 3 t ha-1 and FMA 50 g plant-1 gives growth and yield of sesame is the best on Ultisol.Key words: AMF, Tithonia, Sesamum.